Work-to-non-work spillover: the impact of public service motivation and meaningfulness on outcomes in work and personal life domains. Issue 4 (2nd April 2020) - Zheng, Yuyan; Wu, Chia-Huei; Graham, Les
ABSTRACT: This study examines why, and when, public service motivation (PSM) has spillover effects from employees' work lives into their personal lives. Drawing on a dual conceptualization of meaningfulness, we propose and examine the relationship of PSM with meaningfulness of work through processes of realization and justification. Analyses of 253 matched dyads of policing employees and spouses support the proposed mediation effect of meaningfulness of work from PSM to job satisfaction, individual initiative (i.e. task-related behaviours after work), and psychological detachment from work in non-work time. Job autonomy is found to compensate for PSM in predicting meaningfulness and these outcomes.